Bibliometric Analysis of the Dynamics of Women's Empowerment in the World of Work - Loso Judijanto; Hayu Lusianawati; Salwa Aulia Novitasari (Westscience Press, 2025)
This bibliometric study provides an extensive analysis of the global research trends on women's empowerment in the workforce from 1990 to the present, utilizing the Scopus database. The study identifies key themes, evaluates the evolution of research focuses over time, and maps the collaborative networks among countries engaging in this field. Initially centered on gender roles and employment, the research emphasis has progressively expanded to include intricate links with economic development, health, and human rights, reflecting an interdisciplinary approach. Our findings reveal that the United States, India, and the United Kingdom are pivotal in the scholarly network, demonstrating strong international collaborations. The study highlights the shift towards integrating women's empowerment with broader economic policies and underscores the importance of collaborative research in enhancing the understanding of gender equality issues. This work not only sheds light on the thematic and collaborative dynamics in the field but also suggests directions for future research to foster a more inclusive and comprehensive discourse on gender equality.